2020
DOI: 10.1111/pai.13397
|View full text |Cite
|
Sign up to set email alerts
|

Foetal exposure to heavy metals and risk of atopic diseases in early childhood

Abstract: Background Accumulating evidence suggests that in utero exposures can influence the development of the immune system and thus contribute to disease development. Studies investigating the association between prenatal exposures to heavy metals and atopic diseases, however, are scarce. Methods Children from the EDEN birth cohort were prospectively followed up using parental questionnaires with validated questions on asthma, allergic rhinitis, eczema, and food allergy symptoms. The questionnaires were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Emerging evidence suggests prenatal exposure to heavy metals can influence the development of the child’s immune system and contribute to the development of various disease conditions[ 20 ]. Prenatal exposures to cadmium (Cd), Pb, and/or Hg have been linked to the development of asthma, eczema, food allergy, and adverse respiratory outcomes in children[ 20 - 22 ]. Heavy metals may be transmitted to the fetus during pregnancy via cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests prenatal exposure to heavy metals can influence the development of the child’s immune system and contribute to the development of various disease conditions[ 20 ]. Prenatal exposures to cadmium (Cd), Pb, and/or Hg have been linked to the development of asthma, eczema, food allergy, and adverse respiratory outcomes in children[ 20 - 22 ]. Heavy metals may be transmitted to the fetus during pregnancy via cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiologic studies have reported an increased risk of allergies or asthma in children born to mothers exposed to some environmental chemicals during pregnancy, such as pesticides [ 13 ], perfluoroalkyl acids (PFAAs) [ 44 ], phthalates [ 63 ], trace elements (TE) [ 50 ], polycyclic aromatic hydrocarbons (PAHs) [ 34 ], bisphenol A (BPA) [ 68 ], brominated flame retardants (BFRs) [ 42 ] or polychlorobiphenyls (PCBs) [ 46 ]. Inversely, other studies found a decreased risk of allergy or wheezing related to the prenatal exposure to some PFAAS [ 2 ], pesticides [ 41 ], BFRs [ 43 ], and BPA [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Development of preventive interventions requires profound understanding of the disease mechanisms, including key molecules and pathways. Based on the current consensus, these mechanisms operate already at early life including the in utero period, 15 , 16 when the first subclinical signs of IMDs often appear 17 and when the immune system is under rapid transition from an immature stage to the mature adult stage. As a significant component in these processes, the crosstalk between the commensal microflora 18 , 19 and the child’s maturating immune system has received special attention in the field.…”
Section: Introductionmentioning
confidence: 99%